Ethics of Artistic Collaboration in Cultural Diplomacy Amid Global Conflict: The Collaboration Between the Jakarta Arts Council (DKJ) and the Ukrainian Institute in 2024 - Ivana Noor; Agus Satory (Jurnal Sosial Teknologi, 2026)
Cultural diplomacy has increasingly become an important approach to strengthening international relations through cultural exchange and artistic collaboration. This study examines the ethical dimensions of artistic cooperation in cultural diplomacy through the collaboration between the Jakarta Arts Council (Dewan Kesenian Jakarta – DKJ) and the Ukrainian Institute in 2024. The research aims to analyze how ethical principles shape artistic collaboration and how cultural initiatives function as diplomatic instruments in the context of global conflict. This study employs a qualitative research design, using document analysis and a literature review to explore cultural programs, institutional reports, and scholarly sources related to cultural diplomacy and artistic exchange. The findings indicate that artistic collaboration serves as an effective medium for promoting intercultural dialogue, strengthening international cultural relations, and expanding networks among artists and cultural institutions. Ethical principles such as respect for cultural diversity, neutrality in political contexts, and intercultural dialogue play an important role in ensuring that artistic initiatives remain constructive platforms for cultural communication. However, challenges related to political sensitivity, cultural representation, and institutional coordination may influence the implementation of cultural diplomacy initiatives. Overall, the study demonstrates that ethical artistic collaboration can contribute significantly to cultural diplomacy by fostering cultural understanding and international cooperation, even in times of geopolitical tension.